THE IMPACT OF SOCIAL MEDIA ON MODERN ENGLISH LANGUAGE (Ustozlar uchun, 2026)
This article investigates the impact of social networks on contemporary English. The research results demonstrate that social media rapidly introduce new words and transform classic normative rules of English. For example, emojis, hashtags, abbreviated forms, and internet slang are the most rapidly changing components of English language. The article presents a linguistic analysis of 5000 social media posts throughout 2023 to examine the pace of language change.